2020
DOI: 10.3389/fcell.2020.596831
|View full text |Cite|
|
Sign up to set email alerts
|

TNFR2 Is a Crucial Hub Controlling Mesenchymal Stem Cell Biological and Functional Properties

Abstract: Mesenchymal stem cells (MSCs) have drawn lots of attention as gold standard stem cells in fundamental and clinical researches during the last 20 years. Due to their tissue and vascular repair capacities, MSCs have been used to treat a variety of degenerative disorders. Moreover, MSCs are able to modulate immune cells’ functions, particularly T cells while inducing regulatory T cells (iTregs). MSCs are very sensitive to inflammatory signals. Their biological functions could remarkably vary after exposure to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 95 publications
0
30
0
Order By: Relevance
“…For example, MSCs respond to TGFα/EGF receptor by increasing VEGF production ( De Luca et al, 2011 ). On the other hand, VEGF signaling pathway is defective in TNFR2 KO mice ( Luo et al, 2006 ), and a correlation between TNFR2 expression by MSCs and NO production, that directly induces VEGF, has been recently established ( Beldi et al, 2020a ). Previously, it has been found that VEGF production by TNF-α-primed human bone marrow MSCs was TNFR2 dependent ( Crisostomo et al, 2008 ; Zhang A. et al, 2010 ).…”
Section: Engineering Mesenchymal Stromal Cells For Enhancing Their Thmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, MSCs respond to TGFα/EGF receptor by increasing VEGF production ( De Luca et al, 2011 ). On the other hand, VEGF signaling pathway is defective in TNFR2 KO mice ( Luo et al, 2006 ), and a correlation between TNFR2 expression by MSCs and NO production, that directly induces VEGF, has been recently established ( Beldi et al, 2020a ). Previously, it has been found that VEGF production by TNF-α-primed human bone marrow MSCs was TNFR2 dependent ( Crisostomo et al, 2008 ; Zhang A. et al, 2010 ).…”
Section: Engineering Mesenchymal Stromal Cells For Enhancing Their Thmentioning
confidence: 99%
“…Nevertheless, it is important to clarify more conclusively the relevance of an inflammatory environment for the MSC-mediated immunomodulation. Two recent publications by Naserian and colleagues ( Beldi et al, 2020a , b ) have provided new and relevant information on the role played by TNF-α signaling in these processes. TNF-α exerts its effects through interaction with two receptors, TNFR1 and TNFR2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 126 Moreover, TNFR2-KO MSCs also reduce their proliferation capacity, major characteristics markers (Sca1, CD90, CD105, CD44, and CD73), and functional properties (tissue/cell regeneration functions and endothelial pro-angiogenic support). 127 …”
Section: Other Types Of Tnfr2-expressing Cells In the Tumor Environmentmentioning
confidence: 99%
“…209,210 Due to the lack of expression of co-stimulatory molecules and the production of several anti-inflammatory mediators, MSCs are immunoprivileged, immunosuppressive and possess immunomodulatory properties. [211][212][213] Both immunomodulatory capacity and low immunogenicity are highly advantageous regarding MSCs as a cell source for reseeding decellularized scaffolds. MSCs cultured on the dECM scaffolds could enhance the biocompatibility of the constructs.…”
Section: Recellularization Of Cartilagementioning
confidence: 99%